2006
DOI: 10.1542/peds.2006-1113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combined Therapy of Erythropoietin, Iron, Folate, and Vitamin B12 on the Transfusion Requirements of Extremely Low Birth Weight Infants

Abstract: Combined treatment with erythropoietin, intravenous iron, folate, and vitamin B12 during the first weeks reduces the need for transfusion in extremely low birth weight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 45 publications
1
15
0
10
Order By: Relevance
“…In previous reports, EPO was shown to decrease the number of RBC transfusions in preterm infants [11,18,19,20,21]. Tempera et al [20] reported an association between EPO treatment and a decrease in ventilator days and speculated on the potential to reduce BPD rates [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, EPO was shown to decrease the number of RBC transfusions in preterm infants [11,18,19,20,21]. Tempera et al [20] reported an association between EPO treatment and a decrease in ventilator days and speculated on the potential to reduce BPD rates [20].…”
Section: Discussionmentioning
confidence: 99%
“…They were not designed to detect a difference in BPD outcome. The study by Haiden et al [21], in 40 infants with a BW 450–800 g and GA ≤32 weeks, reported a decrease in transfusions in the EPO group which also had a higher proportion of infants requiring mechanical ventilation. There was no significant difference in incidence of BPD overall (6/21 or 29% vs. 8/19 or 42%).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the dose-response association between injected vitamin B 12 and levels of biomarkers was not estimated. (58) Only data on biomarkers Monsen et al (2006) (59) Does not address any relationships of interest Casanueva et al (2006) (60) Type of intervention: multivitamin supplement Choudhry et al (1972) (61) Study design: intervention but not RCT Cikot et al (2001) (62) Only data on biomarkers Couto et al (2007) (63) Only data on biomarkers Cornel et al (2005) (64) Irrelevant micronutrient Czeizel and Dudas (1992) (65) Type of intervention: multi-vitamin supplement Czeizel and Medveczky (2003) (66) Does not address any relationships of interest Dagnelie et al (1989) (67) Does not address any relationships of interest Dawson et al (2000) (68) Study design: intervention but not RCT van Dusseldorp et al (1999) (69) Study design: case-control study Eilander et al (2010) (70) Study design: cross-sectional study investigating S-H relationship Gomber et al (2003) (71) Study design: cross-sectional study investigating S-H relationship Gomber et al (1998) (72) Study design: cross-sectional study investigating S-H relationship Gordon and Carson (1976) (73) Study design: case report Graham et al (1992) (74) Population group: infants did not meet the inclusion criteria (unhealthy) Haggarty et al (2006) (75) Irrelevant health outcome (76) Type of intervention: multi-vitamin supplement …”
Section: Infantsmentioning
confidence: 99%
“…In addition, although not the primary outcome of the study, 59% of the Darbe recipients and 52% of the Epo recipients did not receive any transfusions during their hospitalization. Although previous studies outside the United States have achieved similar levels of success, 23 this is the first US study to report a .50% transfusion-free population of very low birth weight infants. Moreover, although the number of transfusions has decreased over the past 20 years, extremely low birth weight (ELBW) infants are still receiving 3 to 5 PRBC transfusions per hospitalization, and are being exposed to 2 to 3 donors.…”
Section: Figurementioning
confidence: 62%